Playing games online increases risk of hypertension, tachycardia, and tachypnea - Komang Galang Nadi Sastra; Hendri Kurniawan (Edukasi Ilmiah Indonesia, 2025)
Introduction: Game Online is a virtual world game site connected via the internet. Playing a game online intensely and with a high level of difficulty will trigger an increase in the production of adrenaline hormones, thus affecting blood pressure, pulse rate, and breathing. This study aims to determine the relationship between playing online games and blood pressure, pulse rate, and breathing rhythm. Research Methodology: The study used a quantitative research method, a non-experimental type with a cross-sectional design. The sampling technique was purposive sampling with a sample size of 84 people. The research variables were measured using a digital sphygmomanometer, pulse oximeter, and manual respiratory examination. Data was analyzed using SPSS 25 with the Pearson product-moment test and linear regression. Result: the majority of the sample was playing games online 7 times a week (56%), with a duration of 3 hours a day (41.7%). The results of the Pearson test showed that the intensity of playing online games was positively correlated with blood pressure (p<0.05; r=0.529), pulse rate (p<0.05; r=0.482), and respiration (p<0.05; r=0.269). The results of the linear regression test proved that the intensity of playing online games affected blood pressure (p<0.05; R-square=0.347), pulse rate (p<0.05; R-square=0.232), and respiration (p<0.05; R-square=0.072). Conclusion: It can be concluded that there is a positive relationship between the intensity of playing online games with blood pressure, pulse, and respiratory frequency. The higher the intensity of playing online games, the higher the value of the three physiological indicators. In addition, the intensity of playing online games has also been shown to affect blood pressure, pulse, and breathing. These findings suggest that intensive online gaming activities can have an impact on the body's physiological condition